Lógica fuzzy para modelamento e auxílio no processo de tomada de decisão em caso de derrame de óleo no mar - Leone, Gabriel Correia (2010)
The increase of energy demand makes the society dependent on the use of a nonrenewable natural resource: oil. The search for oil and gas reserves and the removal of this material have social and economic importance. However, in cases of accident, the environmental consequences are sometimes disastrous. Because of these features, the search for mitigation measures to reduce the impacts from the activities help the process of decision making. This work deals with the use of Numerical Model OILMAP for modeling scenarios of containing, recover and fate dispersion in cases of oil accidents under different environmental parameters proportioning information to build a base of rules that support a modeling through Fuzzy Model in a manner that more quickly and faster responses can be achieve. Fuzzy Logic have linguistic values instead numerical values, which adds uncertainty to analysis the problem, better understanding by non-specialists, faster responses and lower computational cost. First, scenarios were simulated by using a numerical model of transport for different environmental conditions, basis for creating a Fuzzy Model. Fuzzy Model results were, in most cases, consistent with the numerical model, denoting computational effort and faster responses, demonstrating that is an important tool for assisting decision making.